Gangsters of Miami: true tales of mobsters, gamblers, hitmen, con men and gang bangers from the Magic City - Chepesiuk, Ron (Barricade Books Inc., 2010)
Prologue: the king of Thunderboat Row -- Beginnings -- The leakiest spot in America -- Scarface in paradise -- Casino royale -- The Cuban mafia -- High times -- Cocaine central -- Follow the money -- Gangsters in blue -- Murder on Thunderboat Row -- Operation cornerstone -- The Russians are coming -- Gang bangers -- True crimes